2011
DOI: 10.1007/978-3-642-17928-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Scalability and Parallelization of Monte-Carlo Tree Search

Abstract: Monte-Carlo Tree Search is now a well established algorithm, in games and beyond. We analyze its scalability, and in particular its limitations, and the implications in terms of parallelization, in particular for our program MoGo but also for our Havannah program Shakti. In particular, we get a good efficiency for the parallel versions, both for multicore machines and for message-passing machines, but in spite of promising results in self-play there are situations for which increasing the time per move does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…We started with the UCB algorithm and this lead to the so-called UCT (Upper Confidence Bounds applied to Trees) algorithm, which was independently developed and analyzed by Csaba Szepesvári and Levente Kocsis [78]. Several major improvements (such as the use of features in the random playouts, the Rapid Action Value Estimation (RAVE), the parallelization of the algorithm, and the introduction of opening books) [56,91,21,97,43,57] …”
Section: Historical Motivation In Computer Gomentioning
confidence: 99%
“…We started with the UCB algorithm and this lead to the so-called UCT (Upper Confidence Bounds applied to Trees) algorithm, which was independently developed and analyzed by Csaba Szepesvári and Levente Kocsis [78]. Several major improvements (such as the use of features in the random playouts, the Rapid Action Value Estimation (RAVE), the parallelization of the algorithm, and the introduction of opening books) [56,91,21,97,43,57] …”
Section: Historical Motivation In Computer Gomentioning
confidence: 99%
“…When information is shared, only a portion of the tree is shared in order to minimise the communication overhead of sharing. A possible sharing strategy is to share the nodes in the top 3 levels that have at least 5% of the total playouts through them, at a frequency of 3 Hz [21]. In this method, each of the processing nodes performs all four steps of the MCTS iterations on its tree.…”
Section: Root Parallelisationmentioning
confidence: 99%
“…If root parallelisation could update at infinite frequency, share the whole tree, and update in zero time, then it would be equivalent to tree parallelisation. Bourki et al have shown root parallelisation to scale to 40 nodes [21]. [23].…”
Section: Root Parallelisationmentioning
confidence: 99%
See 2 more Smart Citations